Consumer choices and demand for tilapia in urban Malawi: What are the complementarities and trade-offs? - Chikowi, Christopher T. M.; Ochieng, Dennis O.; Jumbe, Charles B. L. (International Food Policy Research Institute, 2019)
Despite concerted efforts to develop the fisheries sector in many developing countries, fish demand remains poorly understood due to weak and fragmented domestic markets, particularly in Africa south of the Sahara. An important area that affects the development of the fishery sector is limited understanding of how the choice between different fish products is affected by the socioeconomic characteristics of consumers, marketing factors and fish-specific attributes. Previous studies in Malawi have assessed consumer choice and demand for fish in general, without considering species-specific consumer choices. This paper analyzes consumer choices and demand for two species of tilapia, Lake Malawi Oreochromis (Nyasalapia) spp. (Ny) and Oreochromis shiranus (Os), in unprocessed and processed form, in urban Malawi. We use data collected from a sample of 584 urban households in Malawi’s two major cities, Blantyre and Lilongwe. Multivariate probit and seemingly unrelated regression models are employed to analyze the correlates of consumer choice and demand for tilapia products. Even though most consumers chose farmed tilapia (Os) over the wild tilapia (Ny), our results indicate trade-offs in choice but complementarities in demand for unprocessed and processed tilapia products. We find that the correlates of choice are not the same as correlates of demand for tilapia products. This is explained by heterogenous consumer profiles, market conditions, and tilapia trait descriptors. Developing robust tilapia value chains requires exploiting these complementarities and trade-offs, policy support to boost tilapia production, and reducing its relative caloric price to consumers. These measures will contribute to increased consumer demand. More generally fish breeding programs should also link breeding objectives to consumer choices and demand for fisheries’ products, particularly considering rarely examined fish at-tributes such as its nutritive value and body texture.